Service Quality, Customer Satisfaction, and Repurchase Intention in Atalilah Catering at Belopa City - Ansri Jayanti; Sultan; Yusriani Yusuf; Nina Fapari Arif; Tasrim; Eka Muzalfitri Ridwan (Yayasan Putra Adi Dharma, 2023)
Intention is the first step before making a decision to use a product. This position is primarily determined by the strategy of the company marketing the product. So, encouraging customer buying interest is strategic in